Use of Postoperative TENS Along with Rehabilitation Protocol Following Total Knee Replacement for Better Results (Medico Legal Update, 2021)
Objective: To assess the viability of TENS in diminishing agony and increasing function following TKR.Sample: 30 subjects (age>55years)chose based on consideration and avoidance standardsare included inthe study.Method: 30 subjects were taken in the study,chosen based on consideration and rejection models andarbitrarily assigned to each group. Group 1 and group2. Experimental group (group 1) received TENS andexercise while control group received only exercises for 20 days (6 days per week). Functional testing wasdone using a questionnaire.Results: Paired t-test was used for statistical analysis. There was huge distinction between the two groups(A & B). The experimental group has significant improvement then the observational group. The pain VASscore has more difference. There was no significant difference in ADL activities score.Conclusion: It was concluded that applying TENS along with exercises on initial days of rehabilitationshows better results and increases the recovery process.